Three Distinct Views of Deep Pelagic Community Composition Based on Complementary Sampling Approaches - Hetherington, Elizabeth D.; Choy, C. Anela; Thuesen, Erik V.; Haddock, Steven H. D. (Frontiers in Marine Science, 2022)
Our perception of deep-sea communities has evolved as various sampling approaches have captured different components of deep-sea habitats. We sampled midwater zooplankton assemblages in Monterey Bay, California to quantify community composition (abundance and biomass) and biodiversity (at the Order level) across three depth ranges, and the effects of sampling methodology on community parameters. We collected zooplankton using two types of opening-closing trawls [Tucker Trawl and Multiple Opening/Closing Net and Environmental Sensing System (MOCNESS)] and video recordings from a remotely operated vehicle (ROV). We quantified the relative contributions of microbes to community biomass using synoptic water-bottle casts and flow cytometry. Overall, the pelagic community was most similar between the Tucker trawl and ROV (dissimilarity = 52.4%) and least similar between the MOCNESS and ROV (dissimilarity = 65.8%). Dissimilarity between sampling methods was driven by the relative abundances of crustaceans and gelatinous taxa, where gelatinous animals (cnidarians, ctenophores, tunicates) were more abundant in ROV surveys (64.2%) and Tucker trawls (46.8%) compared to MOCNESS samples (14.5%). ROV surveys were the only method that sufficiently documented the most physically delicate taxa (e.g., physonect siphonophores, lobate ctenophores, and larvaceans). Biomass was also one order of magnitude lower in MOCNESS trawls compared to Tucker trawls. Due to these large differences, the relative contributions of microbes to total biomass were substantially lower in Tucker trawl samples (mean = 7.5%) compared to MOCNESS samples (mean = 51%). These results illustrate that our view of planktonic composition and community biomass is strongly dependent on sampling methodology.